2007
DOI: 10.1002/bdd.551
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of methylprednisolone after intravenous and intramuscular administration in rats

Abstract: Methylprednisolone (MPL) pharmacokinetics was examined in adrenalectomized (ADX) and normal rats to assess the feasibility of intramuscular (i.m.) dosing for use in pharmacodynamic studies. Several study phases were pursued. Parallel group studies were performed in normal and ADX rats given 50 mg/kg MPL (i.v. or i.m.) and blood samples were collected up to 6 h. Data from studies where normal rats were dosed with 50 mg/kg MPL i.m. and killed over either 6 or 96 h were combined to determine muscle site and plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(53 citation statements)
references
References 36 publications
5
47
1
Order By: Relevance
“…The only major difference between the two studies is that the gene expression analysis were performed in animals that were given an intravenous dose of the drug and the proteomic measurements were performed in rats given an intramuscular injection of MPL. However, our previous studies comparing the two routes of MPL dosing indicated that, though there are some early differences in the pharmacokinetic profiles of MPL, the pharmacodynamics of an important biomarker tyrosine aminotransferase (TAT) expressed in liver were comparable (Hazra et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The only major difference between the two studies is that the gene expression analysis were performed in animals that were given an intravenous dose of the drug and the proteomic measurements were performed in rats given an intramuscular injection of MPL. However, our previous studies comparing the two routes of MPL dosing indicated that, though there are some early differences in the pharmacokinetic profiles of MPL, the pharmacodynamics of an important biomarker tyrosine aminotransferase (TAT) expressed in liver were comparable (Hazra et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneous analysis of plasma as well as muscle site PK of MPL in rats revealed incomplete bioavailability and a complex release pattern [24] from the injection site (flip-flop kinetics with two absorption rates) compared to humans [39,40] and even compared to other CS in rats [41]. Despite these complexities in PK via the IM route, examination of TAT dynamics revealed similar IM and IV response profiles [24]. Therefore, the more convenient IM dosing was chosen.…”
Section: Discussionmentioning
confidence: 99%
“…Rats were weighed, anesthetized with ketamine/xylazine, and sacrificed by aortic exsanguinations at 0.25, 0.5, 0.75, 1, 2, 4, 5,6,7,8,12,24,36,48,60,72,84 and 96 h (n = 3 per time point). Six rats injected with IM saline and sacrificed at 12 and 24 h (n = 3 per time point) served as controls.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although absorption of MP from tissues has been reported to be delayed, this consideration does not appear to be significant. 2 The use of MP during the period immediately after SCI with the goal of improving neurological function continues to be a topic of controversy. Evidence of benefit from clinical trials 1 led to use of this intervention in many newly injured individuals with SCI.…”
Section: Mp-induced Atrophymentioning
confidence: 99%